The Legal Protection for Children as Criminal Actors - Robertus David Mahendra Saputra; Jawade Hafidz; Denny Suwondo (Universitas Islam Sultan Agung, 2022)
The purpose of this research is to analyze the legal protection of children as perpetrators of criminal acts, to analyze the obstacles in the legal protection of children as perpetrators of criminal acts, and to analyze solutions to obstacles in the legal protection of children as perpetrators of criminal acts. This research uses a normative juridical approach, with descriptive research methods that are analyzed qualitatively. The research problem was analyzed using the theory of justice and the theory of the operation of law. The results of the study concluded that the form of legal protection given to children as perpetrators in criminal acts is in accordance with Act No. 11 of 2012 concerning Juvenile Justice and the Criminal Code, namely returning to parents (Article 45 of the Criminal Code), rehabilitation, detention processes (Article 32 of Act No. 11 of 2012). The obstacles faced are the psychological condition of the child who is still unstable, the origin of the perpetrator, and the time required to administer the judicial process, and the lack of cooperation and coordination between the perpetrator, the victim, and the Fathers. The solution that can be given is coordination between stakeholders in handling children in conflict with the law (ABH) must be more intense, it is necessary to involve the community and non-governmental organizations (NGOs) in prevention programs and after care programs for children in conflict with the law (ABH), encourage various parties to intensify case resolution using the principle of restorative justice by means of diversion